CORRELATION OF THE LENGTH OF BEING A CADRE, KNOWLEDGE, EDUCATION, TRAINING, SKILLS WITH THE PRECISION AND ACCURACY OF CHILDREN UNDER FIVE'S WEIGHING RESULTS BY INTEGRATED HEALTHCARE POST (POSYANDU) CADRES IN THE WORKING AREA OF BANGKALAN PUBLIC HEALTH CENTER, BANGKALAN DISTRICT, BANGKALAN DISTRICT, INDONESIA - Hariyanti, Hidayaturrifa Febry; Permana Putri, Endah Budi (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACTThe ability and accuracy of Integrated Healthcare Post (Posyandu) cadres in taking anthropometric measurements is critical, this is related to the interpretation of the nutritional status of children. The purpose of this study was to determine the old relationship between being a cadre, knowledge, education, training, skills with precision, and accuracy of the results of weighing under five by Integrated Healthcare Post cadres in the working area of Bangkalan Community Health Center, Bangkalan District, Bangkalan Regency. This type of research is an observational analytic study with a cross-sectional approach method. The results showed (41%) respondents who had long been cadres had good precision, (47%) respondents who had long been cadres had poor accuracy, (10%) had a good knowledge with good precision, (10%) have good knowledge with good accuracy, (7%) have tertiary education with good precision, (7%) have tertiary education with good accuracy, (11%) do frequent training with no precision. good, (43%) did adequate training with poor accuracy, (44%) had unskilled skills with poor precision, (58%) had unskilled skills with poor accuracy. There is a relationship between years of being a cadre, education, skills, training and knowledge with the precision of weighing children under five, there is a relationship between skills and education with the accuracy of weighing results for toddlers Integrated Healthcare Post cadres are expected to add insight related to knowledge and add experience in weighing toddlers. ABSTRAKKemampuan serta ketepatan kader Posyandu pada saat melakukan pengukuran antropometrik sangat penting hal ini akan interpretasi status gizi balita. Tujuan dalam penelitian ini adalah untuk mengetahui hubungan lama menjadi kader, pengetahuan, pendidikan, pelatihan, keterampilan dengan presisi dan akurasi hasil penimbangan berat badan balita oleh kader Posyandu di wilayah kerja Puskesmas Bangkalan Kecamatan Bangkalan Kabupaten Bangkalan.Jenis penelitian ini adalah penelitian analitik observasional dengan metode pendekatan cross-sectional. Hasil penelitian menunjukkan (41%) responden yang lama menjadi kader memiliki presisi baik, (47%) responden yang lama menjadi kader memiliki akurasi tidak baik, (10%) memiliki pengetahuan yang baik dengan presisi baik, (10%) memiliki pengetahuan yang baik dengan akurasi baik, (7%) memiliki pendidikan tinggi dengan presisi baik, (7%) memiliki pendidikan tinggi dengan akurasi baik, (11%) melakukan pelatihan sering dengan presisi tidak baik, (43%) melakukan pelatihan yang cukup dengan akurasi tidak baik, (44%) memiliki keterampilan yang tidak terampil dengan presisi tidak baik, (58%) memiliki keterampilan yang tidak terampil dengan akurasi tidak baik. terdapat hubungan antara lama menjadi kader, pendidikan, keterampilan, pelatihan dan pengetahuan dengan presisi hasil penimbangan balita, terdapat hubungan antara keterampilan dan pendidikan dengan akurasi hasil penimbangan balita. Kader Integrated Healthcare Post diharapkan menambah wawasan terkait pengetahuan serta menambah pengalaman dalam melakukan penimbangan berat badan balita.